2009
DOI: 10.1007/s12272-009-1618-y
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of oligopeptides from hen egg white on both human platelet aggregation and blood coagulation

Abstract: Egg white proteins have many biological functions and substantial nutritional benefits when used as a food source; however, they also contain allergens such as ovalbumin, ovomucoid, and ovotransferrin. We prepared oligopeptides without allergens from hen egg whites via the use of several proteases, and assessed their effects on platelet aggregation and blood coagulation, known to both of which are known to be major risk factors in thrombogenesis. Egg white oligopeptides (EWOP) inhibited collagen-induced human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…A prior study reported that that cAMP inhibits platelet activation, which in turn inhibits integrin activation [31]. We confirmed that cAMP generation was facilitated by oligoporin A treatment.…”
Section: Discussionsupporting
confidence: 86%
“…A prior study reported that that cAMP inhibits platelet activation, which in turn inhibits integrin activation [31]. We confirmed that cAMP generation was facilitated by oligoporin A treatment.…”
Section: Discussionsupporting
confidence: 86%
“…It is in the form of small peptides (less than 3000 Da) and contains more than 91% protein providing easily absorbable amino acids source (Figure 8). An in vitro study showed that Runpep® has anticoagulant activity (reduce the formation of coagulum in blood vessels, reduce the risk of embolism) and helps in lowering the blood platelets aggregations [92,93]. In vitro, it showed dose-dependent vasorelaxant activity of both aortic and mesenteric vascular smooth muscle.…”
Section: Egg White Peptides (Runpep®)mentioning
confidence: 99%
“…Platelets are essential for primary hemostasis and repair of the endothelium (1,2), but they also play a role in the development of cardiovascular diseases such as atherosclerosis and thrombotic events (3). When a blood vessel is damaged by injury or pathological alterations, such as in atherosclerosis, platelets adhere to the site of vascular injury, which triggers the subsequent platelet activation followed by platelet aggregation (4).…”
Section: Introductionmentioning
confidence: 99%